After Covid-2019 Pandemic: Returnee Migrants’ Economy Management on Their Household - Mishra, Manamaaya (Patan Pragya, 2022)
This paper is based on returnee migrants' economic management of their households of ward no. 4 in Gauradaha municipality, Jhapa district. The objectives of this paper are to identify the returnee migrants' economic management of their households and to find out the used of their remittances after the COVID pandemic. The paper used a descriptive and analytical research design with the primary source of data method. The study selected 247 households and 163numbers of forms filled up within one month and used the purposive sampling method (non-probability sampling. These data are analyzed through frequency distribution, cross table and the main output. The paper concludes that the majority of international labour migrants seek better income in cities, job seeking on forced idleness during the part of year and services. They are compelled to send their husbands and sons to gulf countries to earn for the subsistence of the households. After returning, the foreign migrant workers to the homeland by the cause of theCOVID-19 pandemic increase the household workloads the financial problems day by day, when they stay in foreign countries improving their economic status from household to community basis level. However, they have the difficulty in getting government services characterized with corruption like nepotism, favoritism and briberies to secure jobs. Low-paid work and illegal transfer, employment discrimination with respect to colour, age, sex, ethnicity, religion and others are major problems facing migrant workers. Although they are trying to engage different types of income generation works or self-employment t at the different local levels, it is necessary for the developing countries to solve these problems.